A análise da mentira em Agostinho - Blans, Lisiane Sabala (2012)
Lying is a perennial theme of moral philosophy. Due to its frequent practice in the routine of people and institutions, and to its great impact, a philosophical reflection about lying acquires great importance. However, its exact function in the interpersonal and institutional relations, its characterization and legitimacy present themselves as a philosophical challenge, as non trivial philosophical issues. Since the origin of philosophy there were disagreeing opinions about the question of knowing if the act of lying is always acceptable, because, if being veracious does not require explanation, being mendacious does. If, on one hand, Augustine and Kant reject each and every type of lie, considering them as an immoral practice, Plato and Benjamin Constant accepted certain types of lie, since these lies are justified by the context. It means that, even those who show themselves as disposed to accept defined exceptions to the practice of being veracious looked for offering good reasons for the aforesaid exceptions. In the interior of Christian tradition, Augustine rejected each and every kind of lie, not accepting any justification for its practice. Was one of the first thinkers to get closer of a definition and to systematize the lie theme. He developed the lie theme in two treaties, one of them titled “On Lying” (De Mendacio, 395 D.C.), and the other “Against Lying” (Contra Mendacium, 420 D.C.). From such treaties it is proposed an analysis of the Augustinian characterization of lie. Augustine adopts as a starting point, the doubt and by the aid of a dialectic and rhetorical route conducts us to a wide ranging proposal about the theme. His work was composed with the hope of finding necessary and enough characteristics of an objective notion of lie, for beyond each and every probable denial. The Augustine analysis about lie will be enlightened, and, from this, practical cases will be explored in their different levels of complexity. Other thinkers who also use the theme and other issues related to the definition are examined, as the case of the double heart doctrine, as well as correlative themes as the moral luck, the case of silence eloquence, and the application of the fallacy of the slippery slope and the crash of faith in the lie theme.